Bottlenose dolphin Tursiops truncatus group dynamics, site fidelity, residency and movement patterns in the Madeira Archipelago (North-East Atlantic). Issue 2 (19th August 2016) - Dinis, A; Alves, F; Nicolau, C; Ribeiro, C; Kaufmann, M; Cañadas, A; Freitas, L
Abstract : The bottlenose dolphin Tursiops truncatus is one of the most frequently sighted cetacean species in the Madeira Archipelago (North-East Atlantic); however, little is known about its population ecology in these waters. Photo-identification undertaken during systematic, non-systematic and opportunistic surveys conducted between 2001 and 2012 was used to assess group dynamics, site fidelity, residency and movement patterns of bottlenose dolphins in the archipelago. Three different patterns of residency were assigned, based on individual sighting histories. Group size ranged between 2 and 90 individuals (median 12), with no significant monthly difference in group size. All resident dolphins formed a core, complex network with migrant and transient dolphins. In contrast, satellite clusters were formed exclusively by transient individuals. The lagged identification rate (LIR) model indicated that a dolphin remained in the area for an average of 90 days, whereas the average time an individual spent outside the study area was approximately 313 days. The Madeira Archipelago appears to be only a section of a much larger home range for this population, with the dolphins exhibiting three different patterns of occurrence that associate with each other. The information gained about this poorly studied population contributes to the overall knowledge of bottlenose dolphins in insular oceanic habitats.